University-community engagement conference - Hartih, Sakinah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2012)
Government of Malaysia estimates that there are about 1.3 million people with various forms of disability; till 20 10, there were only 280.000 of them who have registered with Department of Social Welfare OKM). Community-based rehabilitation (CBR). a program that empowers persons with disabilities (PWD) to access and benefit from education, employment, health, social and rehabilitation services by using predominantly local resources. A total of 4 28 CBR centres were developed in Malaysia until 20 10, which mostly located in district and rural area. CBR teachers are the direct personnel who teach, train and prepare meals for the PWD. The PWD are frequently affected by nutritional status impairment. A survey to reveal the sociodemographic and nutrition condition in CBR centres in 3 states: Perlis, Pulau Pinang and Perak was carried out. It was aimed to identify the possible nutritional problems and risk factors among the PWD and to highlight the problems faced by the teachers in food and nutrition management. This survey involved 165 CBR teachers from 43 centres. It was conducted by visits to each centre and interview sessions with their teachers. The result of interviews showed that the nutrition knowledge and exposure among CBR teachers were limited. CBR teachers also encountered various nutrition problems among the PWD such as chewing and swallowing difficulties. 'picky' eating behaviour, underweight and overweight ·problem, and insufficient food budget. This phenomenon raises concerns to formulate m~re specific and sustainable interventional strategies for the teachers especially in food and nutrition. As playing part of the role in university-community engagement, innovative and creative approach to empower the individuals and communities with nutritional knowledge is crucial. Mutual contribution and cooperation from each character in the society are needed to bring goodness to the welfare of the PWD.